A = 20102011+1/ 20102012+1 < 20102011+1 + 2009 / 20102012+1+2009
= 20102011+2010/20102012+2010
=2010(2010^2010+1) / 2010(2010^2011+1)
= 2010^2010 + 1 / 2010^ 2011 +1 = B
=> A < B
Như vậy mới đúng nè
Ta có B=2010^2010 + 1/ 2010^2011 + 1 < 2010^2010+1+9/2010^2011+1+9=2010^2011+1/2010^2012+1
Vậy B<A
ta có:\(2010A=\frac{10\left(2010^{2011}+1\right)}{2010^{2012}+1}=\frac{2010^{2012}+2010}{2010^{2012}+1}=\frac{2010^{2012}+1+2009}{2010^{2012}+1}=\frac{2010^{2012}+1}{2010^{2012}+1}+\frac{2009}{2010^{2012}+1}=1+\frac{2009}{2010^{2012}+1}\)
\(2010B=\frac{10\left(2010^{2010}+1\right)}{2010^{2011}+1}=\frac{2010^{2011}+2010}{2010^{2011}+1}=\frac{2010^{2011}+1+2009}{2010^{2011}+1}=\frac{2010^{2011}+1}{2010^{2011}+1}+\frac{2009}{2010^{2011}+1}=1+\frac{2009}{2010^{2011}+1}\)
vì 20102012+1>20102011+1
=>\(\frac{2009}{2010^{2012}+1}<\frac{2009}{2010^{2011}+1}\)
\(\Rightarrow1+\frac{2009}{2010^{2012}+1}<1+\frac{2009}{2010^{2011}+1}\)
=>A<B